2012
DOI: 10.1038/mt.2012.197
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of scAAV Vector Insertion Associated With Oncogenic Events in a Mouse Model for Genotoxicity

Abstract: Recombinant adeno-associated virus (rAAV) vectors have gained an extensive record of safety and efficacy in animal models of human disease. Infrequent reports of genotoxicity have been limited to specific vectors associated with excess hepatocellular carcinomas (HCC) in mice. In order to understand potential mechanisms of genotoxicity, and identify patterns of insertion that could promote tumor formation, we compared a self-complementary AAV (scAAV) vector designed to promote insertional activation (scAAV-CBA-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
68
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 34 publications
(43 reference statements)
2
68
2
Order By: Relevance
“…Our observations offer the most compelling evidence to date that therapeutic gene delivery mediated by AAV can display marked genotoxicity. In contrast to other preclinical studies (16,17), the untreated control heterozygous mice used in this work did not display a strain tendency toward the development of HCC ( Figure 1B and Table 1). The rate of HCC observed in our mice, which had contributions from C57BL/6J, 129Sv/Ev and FVB/N strains, is consistent with previously reported rates of HCC in mice with similar strain backgrounds.…”
Section: Discussioncontrasting
confidence: 87%
See 2 more Smart Citations
“…Our observations offer the most compelling evidence to date that therapeutic gene delivery mediated by AAV can display marked genotoxicity. In contrast to other preclinical studies (16,17), the untreated control heterozygous mice used in this work did not display a strain tendency toward the development of HCC ( Figure 1B and Table 1). The rate of HCC observed in our mice, which had contributions from C57BL/6J, 129Sv/Ev and FVB/N strains, is consistent with previously reported rates of HCC in mice with similar strain backgrounds.…”
Section: Discussioncontrasting
confidence: 87%
“…Using a murine model of β-glucuronidase deficiency (mucopolysaccharidosis type VII), Donsante et al documented an increased rate of HCC formation in mice treated with a therapeutic AAV vector in the neonatal period (10,11). Subsequently, several larger independent investigations designed to investigate AAV-mediated genotoxicity in mice were unable to document an increased risk of tumorigenesis (12,13), but these studies failed to replicate key experimental variables, such as the timing of viral administration, vector configurations, dose, delivery route, and background strain susceptibility to develop HCC (14)(15)(16). Even a study that observed an increase in the development of HCCs after mice were administered AAV reporters concluded that the AAV vectors alone did not contribute to the formation of tumors; rather, Bell et al claimed that the expression of LacZ alone or in combination with vector was causative (17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study, we did not find any clonal insertion in this region, underlining the differences between species and with the use of recombinant AAV. Overall, the present results and the occurrence of HCC in two different mouse models infected by AAV vectors support the role of AAV in liver carcinogenesis by insertional mutagenesis in both humans and rodents 32,33,35,36 .…”
supporting
confidence: 80%
“…48 While the authors did observe HCC formation, and even integration events into cellular oncogenes, the very high background rate of HCC formation and relatively low number of recovered integration events failed to resolve whether rAAV was carcinogenic.…”
Section: Aav and Hcc: An Overview Of Published Studiesmentioning
confidence: 97%